Smart-oriented urban development for urban administrative units and smart urban areas in the urbanization context of Vietnam - Phuong, Nguyen Thi Lan; Nhu, Dao Thi (Edelweiss Applied Science and Technology, 2025)
In the context of rapid urbanization and increasing challenges to urban infrastructure and sustainability in Vietnam, this article aims to propose a context-appropriate, smart-oriented development approach for urban administrative units and urban development areas. Drawing from a comprehensive review of global smart city frameworks and the unique structural characteristics of Vietnamese urban areas, the study adopts a conceptual and policy analysis method to examine the feasibility and adaptation of smart urban models. The findings reveal fragmentation in Vietnam’s smart city implementation, where technology-led approaches often overlook local governance capacities, infrastructure readiness, and spatial planning issues. The paper argues for a phased and locally tailored smart development strategy that aligns with the functional roles and growth stages of each urban unit. It emphasizes the need for balanced urban planning that integrates environmental protection, social equity, and economic efficiency. The study concludes that a data-driven, flexible smart urban system, embedded in local realities, can significantly enhance urban resilience and quality of life. Practically, the article offers a roadmap for Vietnamese cities to navigate smart development more effectively and sustainably, supporting evidence-based policymaking and strategic investment planning.